The relationship between professional quality of life and work environment among nurses in neonate care units - Ahmad Batran; Ibrahim Aqtam; Ahmad Ayed; Moath Abu Ejheisheh (PLoS ONE, 2025)
Introduction The work environment is a critical determinant of the professional quality of life (ProQoL) of Neonatal Intensive Care Unit (NICU) nurses. While compassion satisfaction enhances job satisfaction, burnout and secondary traumatic stress have adverse effects on the well-being of nurses and the quality of care provided to patients. This study explores the relationship between the work environment and ProQoL among NICU nurses working in the West Bank, an area plagued by resource scarcity, political instability, and staffing shortages. Methods A cross-sectional study was conducted among 233 NICU nurses in West Bank hospitals from 9 January 2025 to 27 January 2025. Data were collected using the ProQOL and the Practice Environment Scale of the Nursing Work Index (PES-NWI) and analyzed using descriptive statistics, Pearson correlation, and Cronbach’s alpha with SPSS version 23. Results Most nurses reported average compassion satisfaction (94.8%), burnout (91.0%), and secondary traumatic stress (84.1%). The practice environment was moderately favorable, mean 2.7 (SD = 0.3), with strong Collegial Nurse-Physician Relations, mean 2.8 (SD = 0.5), and low Staffing and Resource Adequacy, mean 2.6 (SD = 0.4). The Spearman’s correlation analysis revealed that a positive relationship existed between the favorable environment and compassion satisfaction (r = 0.747, p < 0.001), while there was a negative correlation with burnout (r = -0.604, p < 0.001) and secondary traumatic stress (r = -0.151, p = 0.021). Discussion The results suggest improving staffing and resources, nurse-physician collaboration, and emotional support, which are vital in improving ProQoL in a highly demanding environment.